Implementasi Kurikulum Bilingual Dalam Meningkatkan Kualitas Bahasa Inggris Di SD Bilingual Muhammadiyah 1 Purwodadi - Azka, Muhammad Yaser Arafat; Ali, Mohammad; Narimo, Sabar (FKIP, PGSD, Universitas Slamet Riyadi, 2023)
There are still some obstacles in implementing a bilingual curriculum Â to improve the quality of English at SD Bilingual Muhammadiyah 1 Purwodadi, including incompetent teaching staff, limited support from parents, differences in student characteristics. There needs to be an assessment to solve the problem experienced. This type of research is qualitative whose procedure is to generate descriptive data. The approach uses case studies. The subject of the study consisted of the Headmaster and the class teacher. Data collection techniques through observation, interviews, and documentation. Data analysis techniques use exploratory descriptives. The results showed that the implementation of the bilingual curriculum at SD Bilingual Muhammadiyah 1 Purwodadi in teaching and learning activities, took place with a sustainable system starting from grade 1 to grade 6 in all subjects. In addition, it is supported by English Convercation activities Â which are carried out on certain days. Supporting factors for the implementation of bilingual programs: 1) high student motivation, 2) provision of facilities and infrastructure, 3) sufficiently good linguistic competence of students. Meanwhile, the inhibiting factors are: 1) incompetent teaching staff, 2) limited support from guardians, 3) differences in student characteristics.